Toward a better theoretical and practical understanding of field players` decision-making in handball: A systematic review - Bonnet, G.; Debanne, T.; Laffaye, G. (Movement & Sport Sciences - Science & Motricité, 2020)
The aim of this review is to summarize current literature about decision-making in handball in order to identify potential gaps in the cognitive domain, and to propose directions for future research. Studies used various methods but rarely specified the theoretical framework. Two theoretical approaches are commonly used to study the decision-making in team sports. The cognitive approach was used in two thirds of the studies reported in this review. It focuses on skills used by a player to respond to different stimuli often in a non-specific context. These skills include attention, memory and perception. As expected, expert players tend to perform better in these cognitive tests compared to novices, especially when the task`s complexity is high. In contrary, the naturalistic approach studies the way the player analyzes a real and experienced situation. The studies look first at the generation of options, for which expert players appear superior. Second, they assess team cognition which concerns the way a decision is integrated into a collective plan. In this paper, we`ve described some practical applications and highlighted the limitations and complementarity of these two approaches to study the importance of expertise in decision-making.